HIGH-FREQUENCY TRANSISTOR OSCILLATORS FOR INDUCTION HEATING AND HARDENING - I. H. Isaev (Литьë и металлургия, 2011)
The main type of generators with extended frequency range from 20 to 80 kHz, which enables to replace electron-tube generators, is described. The advantages of such generators are nated, the main characteristics are given.